FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN IBU HAMIL DALAM MELAKUKAN KUNJUNGAN ANTENATAL CARE : LITERATUR REVIEW - Anisa Fauziah; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
This antenatal examination is carried out at least six times. In the first trimester, two antenatal checks are carried out, the second trimester is one examination; and in the third trimester, three antenatal examinations are carried out. There are several factors related to antenatal care visits. Namely education, knowledge, attitudes, and support from the husband or family. This study aims to determine the factors that influence antenatal care examinations based on the results of the studies conducted—using the literature review method for several national articles limited to the last ten years, namely (2011-2022). From the ten articles used as literature, a significant relationship was found between knowledge, education, attitudes, and husband or family support with ANC visiting behaviour. Health workers are expected to pay more attention to the quality and quantity of ANC counselling for pregnant women, and pregnant women are expected to increase awareness regarding carrying out ANC visits. Ten national articles are used as literature; some factors can influence pregnant women's visits to carry out ANC examinations. These factors include education, knowledge, attitudes, and the support relationship of the husband or family